Investigation of Legionella and Other Pathogenic Microorganisms in Different Departments of a University Hospital: A Prospective Study - Filiz Orak; Ekrem Kireçci; Yavuz Orak; Kezban Tülay Yalçınkaya; Hafize Öksüz (Türk Yoğun Bakim Derneği Dergisi, 2022)
Objective: In this study, it was aimed to investigate Legionella spp. and other pathogenic microorganisms in swab samples taken from different units of a tertiary healthcare hospital between July 25, 2019 and November 1, 2019. Materials and Methods: Ninety-two swab samples were taken from the mechanical ventilator, air conditioner filters, water outlets, and sink faucets in the laboratory, operating room and different intensive care units of the hospital. All samples were centrifuged and inoculated directly onto buffered coal yeast extract agar, a medium selective for Legionella and other conventional media. 16S rRNA sequence analysis was performed for identification at the species level by randomly selecting 6 samples that were positive for Legionella by culture and serological tests. Results: Growth compatible with Legionella spp. colonies was observed in 24 (26.08%) cultures. Only three of the 6 serogrouped samples were confirmed by molecular identification. Two of these were identified as Legionella pneumophila subsp. pneumophila and the other as Legionella anisa. Penicillium spp., Aspergillus flavus, Acinetobacter baumannii, Morganella morganii, Moraxella spp., and Pseudomonas aeruginosa were isolated from the filters of mechanical ventilators and Escherichia coli from a tap sample. Conclusion: Potential Legionella spp. exposure in high-risk patients should be eliminated with increased sampling frequency and effective control measures.